2017
DOI: 10.1515/chem-2017-0007
|View full text |Cite
|
Sign up to set email alerts
|

Effect of pH on Structural, Magnetic and FMR Properties of Hydrothermally Prepared Nano Ni Ferrite

Abstract: Nano nickel ferrite particles were prepared at pH values 1.5, 4, 7, 10, 13 by a hydrothermal method using metal chlorides and NaOH as an oxidant and solution basicity controller. There is a phase transition from hematite to spinel ferrite that begins when the pH reaches 4. The lowest crystallite size (4 nm) was associated with a highest lattice constant (8.345 Å), at pH=4. Whereas maximum crystallite size 64.5 nm corresponds lattice constant of 8.298 Å at pH=10. The highest magnetization (48 emu/g) value was a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(4 citation statements)
references
References 27 publications
0
2
0
1
Order By: Relevance
“…Similar behavior has been observed in previous studies, where the spinel phase increases as pH increases and the α-Fe 2 O 3 phase decreases. For instance, Sadeq H. Lafta 34 synthesized Ni ferrites with varying pH values using the hydrothermal method and observed that the spinel phase started to form at pH 7. Huang et al 33 investigated the effect of pH on the formation of Co-Zn ferrites synthesized through the coprecipitation method.…”
Section: Resultsmentioning
confidence: 99%
“…Similar behavior has been observed in previous studies, where the spinel phase increases as pH increases and the α-Fe 2 O 3 phase decreases. For instance, Sadeq H. Lafta 34 synthesized Ni ferrites with varying pH values using the hydrothermal method and observed that the spinel phase started to form at pH 7. Huang et al 33 investigated the effect of pH on the formation of Co-Zn ferrites synthesized through the coprecipitation method.…”
Section: Resultsmentioning
confidence: 99%
“…Саме синтез композиційних феритів призводить до поліпшення їх функціональних властивостей. Розподіл катіонів Ni 2+ , Mn 2+ та Zn 2+ по тетраедричних та октаедричних позиціях має суттєвий вплив на функціональні властивості [11].…”
Section: вступunclassified
“…24 It acquired its significance due to its homogeneous deposition, cost-effectiveness, environment-friendliness, ease of expansion, good crystallization, pure end product, precise control of the size, and morphology control depending on the crystal growth condition. [25][26][27] In hydrothermal processes, reaction conditions, such as solvent, temperature, 28 time, 29,30 pH value, 31 precursor concentrations, and the composition of the precursors, 32,33 have important effects on products. The hydrothermal technique is an excellent alternative to the traditional crystal growth techniques, which are capable of growing a wide range of crystals at temperatures well below their melting points and, therefore, crystals with low thermal stress.…”
Section: Introductionmentioning
confidence: 99%